Penggunaan Media Pembelajaran Aplikasi Video Dalam Meningkatkan Minat Belajar Siswa Di MIN 7 Nganjuk - Diana Rahmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to determine the use of video application learning media in increasing student interest in learning at MIN 7 Nganjuk. The results of the research show that the implementation of the use of Video Application Learning Media at MIN 7 Nganjuk involves planning, implementation and evaluation. Initial, initial, and final activities are the beginning of the implementation process. The learning process then takes the form of an animated video based on the learning material and equipped with cartoon images, sound and writing. Compared to before using animated learning videos, learning with these videos will be better and run more smoothly. Increasing students' interest in learning by using animated videos in learning shows that students respond more quickly to the material taught by the teacher. An animated video is displayed when the teacher finishes showing the video to students and asks questions about it. As a result, students participate actively in class and the atmosphere is pleasant. The number of students who answer the teacher's questions after the animated learning video is shown shows an increase in students' interest in learning. Apart from that, participating in the learning process can excite students.